A Contribution to the Genesis of Analcite after Leucite in Potassic Volcanic Rocks of the Nadik Area, Kerman, Iran (Journal of Sciences, Islamic Republic of Iran)
The origin of analcite-bearing lavas and potassic volcanic rocks is controversial in the geological record. Two main hypotheses are either primary analcite or replacement pseudomorphous of leucite. Spectacular large (5 cm) euhedral trapezohedra occur as single crystals of analcite in tephriphonolite lavas from Nadik area. Based on the following evidences the large analcite trapezohedra from Nadik area are interpreted as having formed by ion-exchange pseudomorphous replacement of primary leucite either during cooling or shortly afterwards. The absence of hydrous primary igneous minerals such as amphibole or mica, lack of evidence for rapid transport of crystals from the depths indicates the stability of the field for analcite. This indicates that primary crystallization of analcite would necessitate crystallization of a sodic pyroxene rather than diopside and preponderance of K2O over Na2O in bulk rock composition. Also, the homogeneous nature of the large single crystals of analcite and lack of effect on the other phases included in analcite, point out to its hydrothermal origin. The tertiary rocks from Nadik have initial 87Sr/86Sr ratios between 0.70453 and 0.70576 and the ?Nd values range from +1.3 to +4.1. Most of the potassic rocks from the Nadik show high Al2O3, K2O, LFSE and LREE abundances and low abundances of TiO2 and HFSE (Ta, Nd and Zr), in addition to LREE>Nb and Zr>Y, these features provide strong evidence of involvement of subduction-related process in the generation of orogenic analcite-bearing potassic magma in the Nadik area.